Contesting the Secular West: Religio-cultural Identity Politics in Western Liberal Democracies - Mullins, Nicholas Alan (Zeitschrift für Religion, Gesellschaft und Politik, 2019)
The interplay of secularism, religion and cultural identity in the contemporary politics of Western liberal democracies must be considered where these important features have been otherwise neglected. As religion has gained salience in both media and popular discourse, so has its influence in both national and global politics. What has been overlooked is that the United States and European countries alike, in confronting growing diversity and multiculturalism, are entangled with contemporaneous debates over culture, nation, and national identity. Secularism and the religio-cultural histories in these societies are thus critical to any discussion surrounding the emergent political trends in these states, given professed secular claims to equality under law, fairness, and neutrality on religious, non-religious, and other grounds. This paper explores the theoretical discourse to draw attention to the relationship between religion, politics, and national identity in the present era.